Biomarkers identification for acute myocardial infarction detection via weighted gene co-expression network analysis. Issue 47 (November 2017) - Zhang, Shu; Liu, Weixia; Liu, Xiaoyan; Qi, Jiaxin; Deng, Chunmei
Abstract : Abstract: The study aimed to seek potential biomarkers for acute myocardial infarction (AMI) detection and treatment. The dataset GSE48060 was used, consisting of 52 peripheral blood samples (31 AMI samples and 21 normal controls). By limma package, differentially expressed genes (DEGs) between 2 kinds of samples were identified, followed by enrichment analysis, subpathway analysis, protein–protein interaction (PPI) network analysis, and transcription factor network (TFN) analysis. Weighted gene co-expression network analysis was used to further extract key modules relating to AMI, followed by enrichment and TFN analyses. Expression validation was performed via meta-analysis of 2 datasets, GSE22229 and GSE29111. A set of 428 DEGs in AMI were screened out, and the upregulated toll-like receptor ( TLR ) family genes ( TLR1, TLR2, and TLR10 ) were enriched in wound response, immune response and inflammatory response functions, and downregulated genes ( GBP5, CXCL5, GZMA, CCL5, and CCL4 ) were correlated with immune response. CCL5, GZMA, GZMB, TLR2, and formyl peptide receptor 1 (FPR1) were predicted as crucial nodes in the PPI network. Signal transducer and activator of transcription 1 (STAT1) was the key transcription factor (TF) with multiple targets. The grey module was highly related to AMI. Genes in this module were closely related to regulation of macrophage activation, and spermatogenic leucine zipper 1 (SPZ1) was identified as a TF. Expressions of TLR2 and FPR1 were confirmed via the integrated matrix. Several potential biomarkers for AMI detection were identified, such as GZMB, GBP5, FPR1, TLR2, STAT1, and SPZ1 . They might exert their functions via regulation of immune and inflammation responses. Genes in grey module play significant roles in AMI via regulation of macrophage activation.